A long and winding road: making cannabis black markets legal - Jeremias Lachman; Andrés López; Sebastián Gómez-Roca (Cahiers des Amériques Latines)
In recent years, cannabis legalization has made progress in different countries. Legalization aims at generating new business opportunities and tax revenues as well as reducing or eliminating the illegal market. Some Latin American governments which joined this wave also had the objective of promoting investments and exports. However, these expectations have yet to be fully validated. Although investments have arrived, so far export activity is very weak and domestic markets are still small. The objective of this paper is to show that even when the demand, the entrepreneurship and the technical knowledge needed to develop a cannabis industry were available, the creation of the institutional infrastructure required for guaranteeing a sound transition from black to legal markets has been a slow process of trial and error, which has curbed growth rates in this new industry. While cannabis offers an opportunity for productive diversification in the region, the design of the appropriate institutional setting for seizing that opportunity demands time and strong interactions among the sector’s stakeholders.